(untitled) (CIPEEX, 2024)
IN THE CONTEXT OF CONSTANT EVOLUTION, THE CONTEXTUALIZATION OF FINANCIAL EDUCATION (FE) IN PERSONAL FINANCIAL CONTROL IS IMPORTANT FOR ANALYZING THE BEHAVIORAL PERSPECTIVE OF EACH INDIVIDUAL. THE UNDERSTANDING OF FINANCIAL CONCEPTS AND THE PROMOTION OF INFORMED DECISIONS FOR THE WELL-BEING OF THE INDIVIDUAL AND SOCIETY ARE BASED ON KNOWLEDGE ACQUIRED IN THE SCHOOL ENVIRONMENT, WHICH IS WHAT THIS NARRATIVE LITERATURE REVIEW DOES. THE CHALLENGES OF FINANCIAL MANAGEMENT IN BRAZIL, ESPECIALLY AMONG UNIVERSITY BUSINESS STUDENTS, HIGHLIGHT THE IMPORTANCE OF FE, WHICH GOES BEYOND SPENDING, SEEKING TO DEVELOP SKILLS TO ACHIEVE GREATER PROFITABILITY. STUDIES ON INVESTMENT DECISION-MAKING HAVE HISTORICALLY BEEN INFLUENCED BY BEHAVIORAL BIASES, CONSISTING OF MANAGING THE FINANCIAL PORTFOLIO MORE EFFICIENTLY, ASSOCIATED WITH UNDERSTANDING THE INVESTOR’S PROFILE, ASSESSED BY QUESTIONNAIRES SUCH AS THE INVESTOR PROFILE ANALYSIS (IPA). THE PROPOSED OBJECTIVE IS TO SEARCH FOR STUDIES THAT ADDRESS THE INVESTMENT KNOWLEDGE OF UNIVERSITY STUDENTS, ESPECIALLY BUSINESS STUDENTS, IN ORDER TO ELUCIDATE INFORMATION GAPS AND POTENTIAL AREAS FOR IMPROVING INVESTMENT KNOWLEDGE. THE METHODOLOGICAL STRATEGY IS A NARRATIVE LITERATURE REVIEW, WITH A QUALITATIVE APPROACH TO BETTER UNDERSTAND THE COMPLEXITY OF THE IDEA AND A DESCRIPTIVE PERSPECTIVE PRESENTING THE CHARACTERISTICS OF A GIVEN THEME. IT TAKES INTO ACCOUNT THE SEARCH IN ONLINE JOURNALS, INCLUDING PERIODICALS CAPES, SCIELO AND GOOGLE SCHOLAR, COVERING THE PERIOD FROM 2019 TO 2023. THE RESULTS MAKE IT CLEAR THAT, WHEN IT COMES TO PERSONAL FINANCE, FINANCIAL PLANNING IS ADDRESSED AS A FUNDAMENTAL FACTOR, AS WELL AS INVESTMENTS THAT BRING WITH THEM A PROFITABLE WAY OF USING MONEY TO ACCUMULATE FUTURE RESOURCES. FROM THIS POINT OF VIEW, STUDIES SHOW THAT AMONG UNIVERSITY STUDENTS, FINANCIAL MATHEMATICS IS THE AREA THEY REMEMBER MOST, YET THEY STILL FEEL NERVOUS, TENSE AND INSECURE. IN CONTRAST TO THIS RESULT, ONE STUDY SHOWS DISSATISFACTION WITH FINANCIAL KNOWLEDGE, BUT RECOGNIZES THE IMPORTANCE OF FE IN A CONSERVATIVE PROFILE. ANOTHER ANALYSIS HIGHLIGHTS THE EMPHASIS ON THE SECURITY OF PERSONAL FINANCES, ACQUIRED THROUGH VARIOUS SOURCES, INCLUDING MAGAZINES, THE INTERNET AND PRACTICAL EXPERIENCE AT HOME. THEREFORE, DESPITE THE AIM OF EXPLORING INVESTMENT KNOWLEDGE AMONG BUSINESS STUDENTS, THE RESULTS GENERALLY INDICATE A LEVEL OF UNDERSTANDING OF FINANCE THAT NEEDS TO BE IMPROVED, AS STUDENTS ARE SEEKING KNOWLEDGE INDEPENDENTLY. THIS HIGHLIGHTS THE IMPORTANCE OF OFFERING QUALIFIED SUPPORT TO STUDENTS, ENCOURAGING THE SEARCH FOR INFORMATION AND PROVIDING ACCESSIBLE EDUCATIONAL RESOURCES, AS WELL AS REAL-LIFE SITUATIONS AND EXAMPLES THAT CAN CONTRIBUTE TO PERSONAL GROWTH. THE NEED FOR MORE DETAILED RESEARCH IS RECOGNIZED IN ORDER TO CONTRIBUTE TO THE IMPROVEMENT OF ACADEMIC CURRICULA AND THE FORMULATION OF EDUCATIONAL POLICIES TO PROMOTE FINANCIAL LITERACY AMONG YOUNG PEOPLE.